Evolution of HD-ZIP transcription factors and their function in cabbage leafy head formation - Zhang, Ju; Chen, Can; Yang, Qihang; Xu, Jie; Han, Zizhuo; Ma, Wei; Zhang, Xiaomeng; Xu, Kedong; Zhao, Jianjun; Chen, Xueping (Frontiers in Plant Science, 2025)
IntroductionThe HD-ZIP protein, a unique class of transcription factors in plants, plays a crucial role in plant growth and development. Although some HD-ZIP transcription factors have been associated with leafy head formation in Chinese cabbage, their regulatory mechanisms remain poorly understood.MethodsThis study identified the HD-ZIP family using HMM and TBtools, constructed a phylogenetic tree with OrthoFinder, and analyzed gene family expansion and contraction using CAFE. Conserved features were analyzed with MAFFT, MEME, and TBtools; regulatory networks were predicted using ATRM and PlantTFDB; and gene expression was validated by qRT-PCR.Results and discussionIn this study, HD-ZIP gene sequences from 87 species were analyzed to explore the evolutionary history of this gene family. Despite significant variation in gene family expansion and contraction across species, our findings indicated that HD-ZIP family proteins were conserved in both lower (Charophyta) and higher plants, where they were potentially involved in root, stem, and leaf differentiation. In our analysis of 22 Brassica species, HD-ZIP III protein sequences and domains were conserved. However, within the pan-genome A of 18 Brassica rapa species, differences were observed in auxin-related cis-elements within the HD-ZIP III promoter regions between heading and non-heading cabbage varieties. RNA-seq analysis of wild-type A03 (heading) and mutant fg-1 (non-heading) revealed that 131 genes formed a protein interaction network or clustered in the same branch as HD-ZIP family genes. Through GO enrichment and qRT-PCR, several key candidate genes of Brassica rapa ssp. pekinensis A03 associated with leafy head formation in cabbage were identified. These findings established a foundation for understanding the molecular mechanisms by which the HD-ZIP gene family regulated head growth in Chinese cabbage.